Effects of heat stress on development, quality and survival of Bos indicus and Bos taurus embryos produced in vitro - Silva, C. F. [UNESP]; Sartorelli, E. S. [UNESP]; Castilho, A. C S [UNESP]; Satrapa, R. A. [UNESP]; Puelker, R. Z. [UNESP]; Razza, E. M. [UNESP]; Ticianelli, J. S. [UNESP]; Eduardo, H. P.; Loureiro, B. [UNESP]; Barros, C. M. [UNESP] (Elsevier, 2013)
Heat stress is an important cause of poor development and low survival rates in bovine embryos. Experiments were conducted to test the hypothesis that Bos indicus embryos are more resistant to heat stress than are Bos taurus embryos. In experiment 1, Nelore and Jersey embryos from oocyte pick-up-derived oocytes were submitted to heat stress (96 hours post-insemination, 41 °C, 6 hours), developmental ratios were assessed at Day 7 (Day 0 = day of fertilization), and blastocysts were frozen for RNA extraction. Experiment 2 evaluated expression of COX2, CDX2, HSF1, and PLAC8 in previously frozen blastocysts. In experiment 3, Nellore and Angus embryos from oocyte pick-up-derived oocytes were submitted to heat stress (96 hours post-insemination, 41 °C, 12 hours) and transferred to recipients on Day 7. In experiment 4, embryos developed as in experiment 3 were fixed for Terminal deoxynucleotidyl transferase dUTP nick end labeling labeling and total cell counting. In experiment 1, heat stress decreased the percentage of Jersey oocytes that became blastocysts, but had no effect on Nellore embryos (34.6%, 25.0%, 39.5%, and 33.0% for Jersey control, Jersey heat-stressed, Nellore control, and Nellore heat-stressed oocytes, respectively; P < 0.05). In experiment 2, heat stress decreased (P < 0.05) expression of CDX2 and PLAC8, with higher expression of these genes in Nellore embryos than in Jersey embryos. Heat stress also decreased (P < 0.05) expression of COX2 in Jersey embryos, but had no effect on Nellore embryos. Expression of HSF1 was decreased (P < 0.05) by heat stress in both breeds, with a greater effect in Nellore embryos. In experiment 3, heat stress tended (P = 0.1) to decrease the percentage of pregnancies among cows (Day 30 to 35) that received Angus embryos. In experiment 4, heat stress increased (P < 0.05) the percentage of apoptotic blastomeres, but had no breed-specific effects. In addition, Nellore embryos had fewer (P < 0.05) Terminal deoxynucleotidyl transferase dUTP nick end labeling- positive blastomeres than did Angus embryos. We concluded that the detrimental effects of heat stress were dependent upon embryo breed and were more evident in Bos taurus embryos than in Bos indicus embryos. © 2013 Elsevier Inc.
Keywords: Bos indicus; Bos taurus; Bovine; Embryos; Heat stress; animal; animal disease; animal embryo; apoptosis; blastocyst; cattle; comparative study; embryo development; embryo transfer; female; fertilization in vitro; gene expression; heat; oocyte; physiology; prenatal development; species difference; Animals; Apoptosis; Blastocyst; Cattle; Embryo Transfer; Embryo, Mammalian; Embryonic Development; Female; Fertilization in Vitro; Gene Expression; Hot Temperature; Oocytes; Species Specificity; Bovinae